From dysphoria to dignity: A case report on bilateral double incisional mastectomy with free nipple-areola graft in a transgender male - Lamsal, Ashbin; Shrestha, Jayan Man; Sharma, Binita (Journal of Gandaki Medical College-Nepal, 2026)
Gender-affirming chest surgery is one of the procedures in the management of transgender male with gender dysphoria. Bilateral double-incision mastectomy with free nipple–areola complex (NAC) grafting is commonly indicated in individuals with large or ptotic breasts to achieve better outcome. We report a case of a transgender male who underwent bilateral double-incision mastectomy. Preoperative assessment was performed using World Professional Association for Transgender Health (WPATH) Standards of Care Version 8 (SOC-8). The procedure involved excision of breast tissue via inframammary incisions, contouring of the chest wall, and harvesting and grafting of the NAC as full-thickness grafts at anatomically appropriate positions. The postoperative period was uneventful, with satisfactory graft uptake and good patient satisfaction. This procedure is a safe and effective technique for chest masculinization in transgender men with moderate to large breasts. It provides reliable aesthetic results with acceptable complications, when performed with appropriate patient selection and surgical expertise.